Familias disfuncionales y su relación con el desarrollo socio-afectivo en estudiantes del octavo año paralelo “B” de la escuela de educación básica Montevideo, Buena Fe 2021 - Vélez Alarcón , . Graciela Cecilia (2022)
The project entitled Dysfunctional families and socio-affective development in students of the eighth parallel year "B" of the Montevideo Educational Unit, Buena Fe, 2021, During the last years some changes in the constitution of the family and decrease of the academic performance have been reported in the students' life records, which have called the attention and coincide with problems of dysfunctionality of their families, therefore the project has as main objective to determine the influence of dysfunctional families in the socio-affective development of the students, The socio-affective state of students with dysfunctional families was diagnosed in students of the eighth parallel year "B" of the Educational Unit Montevideo, Buena Fe, through a survey which resulted in the need to address the motivation of students to improve their emotional development. The methods used in the development of the project are: Inductive method allowed to know the premises of dysfunctional families and socio-affective development in students addition to the Deductive method allowed to generate ideas about the existence of students with socio-affective development problem in students and how they are evaluated and addressed by the teacher, from them generate conclusions on the issue raised, the evaluation of the proposal allowed to know